The Use of Ultrasounds in Improving the Sanitary Quality of Sewage Sludge - Eliza Hawrylik (Proceedings, 2019)
The aim of this article is to study the effect of low-frequency ultrasound on the disintegration of microorganisms present in mixed sewage sludge. Initial and excessive sewage sludge were used for examinations coming from the Bialystok Sewage Treatment Plant. They were exposed to ultrasound at 20 and 40 kHz, in varying sonification times and in the case of variable operation of the ultrasonic cleaner (continuous and pulsating work). Research showed that ultrasound was demonstrating effective action with the tested microorganisms. The 30-minute interaction of ultrasounds at 20 kHz on the bacteria present in sewage sludge resulted in a significant decrease in the number of these microorganisms. The obtained results, therefore, indicate the possibility of using this method to disintegrate microorganisms in municipal wastewater treatment plants.